2002
DOI: 10.1097/00008469-200204000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption and cancers of the bladder, colon and rectum

Abstract: Coffee has been observed to be associated weakly or not at all with bladder cancer risk, inversely with colon cancer risk, and inconsistently with rectal cancer risk. The association between these cancers and consumption of coffee and tea was examined in a single case-control study conducted in Ontario, Canada from 1992 to 1994. A questionnaire was filled out by 927 bladder cancer cases, 991 colon cancer cases, 875 rectal cancer cases, and 2118 population controls. Although bladder cancer risk was not associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 49 publications
0
35
0
2
Order By: Relevance
“…Figure 1 shows flowchart of study section. Of initially 72 studies searched, 13 studies including a total of 12,636 cases and 38,419 controls were identified (Kato et al, 1990;Baron et al, 1994;Ji et al, 1997;Tavani et al, 1997;Inoue et al, 1998;Munoz et al, 1998;Slattery et al, 1999;Woolcott et al, 2002;Zhang et al, 2002;Il'yasova et al, 2003;Li et al, 2011;Wu et al, 2011;. Table 1 summarized the detailed characteristics of included studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows flowchart of study section. Of initially 72 studies searched, 13 studies including a total of 12,636 cases and 38,419 controls were identified (Kato et al, 1990;Baron et al, 1994;Ji et al, 1997;Tavani et al, 1997;Inoue et al, 1998;Munoz et al, 1998;Slattery et al, 1999;Woolcott et al, 2002;Zhang et al, 2002;Il'yasova et al, 2003;Li et al, 2011;Wu et al, 2011;. Table 1 summarized the detailed characteristics of included studies.…”
Section: Discussionmentioning
confidence: 99%
“…All of included 13 studies were published in English, the cases were histological, pathologically or cytological confirmed as CRC. Controls were mainly healthy populations, and matched with age and gender, 4 were hospital-based (HB) (Tavani et al, 1997;Inoue et al, 1998;Munoz et al, 1998;Zhang et al, 2002), 9 were population-based (PB) (Kato et al, 1990;Baron et al, 1994;Ji et al, 1997;Slattery et al, 1999;Woolcott et al, 2002;Il'yasova et al, 2003;Li et al, 2011;Wu et al, 2011;. There were 5 studies performed in China (Ji et al, 1997;Zhang et al, 2002;Li et al, 2011;Wu et al, 2011;, two in Japan (Kato et al, 1990;Inoue et al, 1998), two in the USA (Slattery et al, 1999;Il'yasova et al, 2003), one in Sweden (Baron et al, 1994), one in Italy (Tavani et al, 1997), one in Argentina (Munoz et al, 1998), and one in Canada (Woolcott et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Michels et al (36) reported separate RR from two large US cohorts in their study, the Nurses' Health Study (NHS) (36a) and the Health Professionals Follow-up Study (HPFS) (36b) ; we counted the report as two prospective studies. Finally, our meta-analysis included twenty-five case-control (11,15,20,26,(28)(29)(30)(31)(33)(34)(35)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and sixteen cohort studies (17,19,21-25,27,32,36a,36b,37,52-55) .…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The items in the form included: first author's last name; year of publication; country of origin; years of study/ follow-up period; number of cases/controls; age at baseline; OR/RR and 95 % CI for the association between coffee consumption and colorectal cancer incidence, considering two exposure levels (highest v. lowest/non); type of controls; and control of confounding factors. If OR and/or 95 % CI were not reported, but numbers of cases and controls in highest v. lowest/non categories of coffee consumption were provided, these data were used to calculate crude OR and unadjusted CI (28,31,(33)(34)(35)39,40,42,46,48,49) .…”
Section: Data Extractionmentioning
confidence: 99%